Digitalisasi Lembaga Keuangan Mikro dan Dampaknya terhadap Akses Pembiayaan Usaha Kecil dan Menengah - Farisah Keke Nola Padang; Fitri Hayati; Dimas Ardika; M. Fikri Tanjung (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study examines the role of digitalization of Microfinance Institutions (MFIs) in increasing access to financing for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The study was conducted through a literature review of more than 20 scientific articles, policy reports, and previous research results published between 2020 and 2025. The results indicate that the implementation of digitalization in MFIs can accelerate the financing service process, reduce operational costs, and expand service reach to remote areas previously difficult to reach by conventional financial institutions. The use of technologies such as digital lending, digital credit scoring, and electronic transaction recording has been proven to increase operational efficiency and the accuracy of MSME business feasibility analysis. However, the implementation of digitalization still faces various obstacles, including low levels of digital literacy among MSMEs, limited human resources in MFIs, and increased risks to data security and protection. Therefore, this study emphasizes the importance of strengthening digital infrastructure, increasing human resource capacity, and strategic collaboration between MFIs and fintech companies to realize inclusive and sustainable MSME financing.